2012
DOI: 10.1177/0143034311429167
|View full text |Cite
|
Sign up to set email alerts
|

Using computer-assisted interviewing to consult with children with autism spectrum disorders: An exploratory study

Abstract: This article explores the use of computer-assisted interviewing (CAI) as a tool for consulting with children with autism spectrum disorders (ASD). This is considered within the context of a research study which utilized one CAI programme, In My Shoes, to investigate children and young people's views of provision, support, and participation in meetings and involvement in decision making. Based on a process of reflection through dialogue, the authors report on the perceived value of this methodology compared wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
33
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 41 publications
1
33
0
1
Order By: Relevance
“…Fifty-three (56%) of these participants were male, and seven (8%) were female; thirty-four (36%) participants' genders had not been identified. The following skills were determined as the target skills in the scrutinized studies: (a) interview for counseling (Barrow & Hannah, 2012), (b) visual-spatial skills (Chabani & Hommel, 2014), (c) cooperation with peers (Shih, Chiang, & Shih, 2015), (d) recognizing others (Holt & Yuill, 2014), (e) job interviews in a virtual environment (Smith et al, 2014), and (f) use of computeraided activity schedules (Ülke-Kürkçuoğlu, Bozkurt, & Çuhadar, 2015). A brief analysis of computer-aided instruction of other skills is displayed in Table 4.…”
Section: Studies Conducted Over Individuals With Asd Using Computersmentioning
confidence: 99%
See 2 more Smart Citations
“…Fifty-three (56%) of these participants were male, and seven (8%) were female; thirty-four (36%) participants' genders had not been identified. The following skills were determined as the target skills in the scrutinized studies: (a) interview for counseling (Barrow & Hannah, 2012), (b) visual-spatial skills (Chabani & Hommel, 2014), (c) cooperation with peers (Shih, Chiang, & Shih, 2015), (d) recognizing others (Holt & Yuill, 2014), (e) job interviews in a virtual environment (Smith et al, 2014), and (f) use of computeraided activity schedules (Ülke-Kürkçuoğlu, Bozkurt, & Çuhadar, 2015). A brief analysis of computer-aided instruction of other skills is displayed in Table 4.…”
Section: Studies Conducted Over Individuals With Asd Using Computersmentioning
confidence: 99%
“…Among the scrutinized studies, only one had implemented activity research (Barrow & Hannah, 2012). In the study conducted by Holt and Yuill (2014), the between-subjects repeated-measures design (within-subjects design) was used.…”
Section: Studies Conducted Over Individuals With Asd Using Computersmentioning
confidence: 99%
See 1 more Smart Citation
“…CAPI approaches using handheld tablets or rugged laptop computers to facilitate survey delivery by enumerators, have been widely applied in other fields [16][17][18] and are becoming more common in WaSH research, but the majority of studies are still performed using paper-based surveys, or pen and paper interviewing (PAPI). No studies were found that employed CAPI to investigate household water management.…”
Section: Introductionmentioning
confidence: 99%
“…Los procedimientos de evaluación computarizada son comunes en psicología para valorar distintos aspectos del funcionamiento cognitivo o en el ámbito clínico (e.g., Barrow, 2012;Courtney, Dinkins, Allen y Kuroski, 2003;Kobak, Reynolds y Greist, 1994;Mollicaa, Maruffab, Colliebc y Vancede, 2005;Skuse et ál., 2004;Vispoel, 2000;Visu-Petra, Benga, Fincaş y Miclea, 2007). A pesar del atractivo que supone este tipo de herramientas, que se caracterizan por su versatilidad y que presuntamente aportan confiabilidad y agilidad a la evaluación de diferentes repertorios, existe cierto escepticismo acerca de su pertinencia (Olson-Buchanan y Drasgow, 1999).…”
Section: Introductionunclassified